2019
DOI: 10.1080/14786419.2019.1636242
|View full text |Cite
|
Sign up to set email alerts
|

Anti-melanogenic activity of ellagitannin casuarictin in B16F10 mouse melanoma cells

Abstract: Ellagitannins such as casuarictin (CAS), isolated from clove extracts, have been shown to have superior benefits such as antioxidant and anti-inflammatory activity, but there have been no reports on their capacity to inhibit melanogenesis.Inhibition of melanogenesis by novel natural products has gained attention for cosmetic applications such as skin lightening. Here, we report the effects of CAS on melanogenesis in B16F10 mouse melanoma cells. Our results showed that CAS (30µM) significantly inhibited intrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
2
9
0
Order By: Relevance
“…At present, though a wide range of tyrosinase inhibitors from natural and synthetic sources have been reported, only a few of them, in addition to being effective, are known as safe compounds. No significant advances concerning toxicity issues of tyrosinase inhibitors seem to emerge from the literature survey carried out for this review, the relevant papers just reporting the results of in vitro cytotoxicity experiments [49,52,75,81,95,126,129,[131][132][133]136,137,147,163,[176][177][178]184,185,192,198,202,203,207,210,212,214,215,239,240,242,245] and only a few of in vivo experiments on zebrafish [130,206,209]. Therefore, it is essential to examine the efficacy and safety of inhibitors by checking e.g., whether or not the candidate inhibitor is substrate of tyrosinase being modified on exposure to the enzyme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, though a wide range of tyrosinase inhibitors from natural and synthetic sources have been reported, only a few of them, in addition to being effective, are known as safe compounds. No significant advances concerning toxicity issues of tyrosinase inhibitors seem to emerge from the literature survey carried out for this review, the relevant papers just reporting the results of in vitro cytotoxicity experiments [49,52,75,81,95,126,129,[131][132][133]136,137,147,163,[176][177][178]184,185,192,198,202,203,207,210,212,214,215,239,240,242,245] and only a few of in vivo experiments on zebrafish [130,206,209]. Therefore, it is essential to examine the efficacy and safety of inhibitors by checking e.g., whether or not the candidate inhibitor is substrate of tyrosinase being modified on exposure to the enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the direct inhibition of tyrosinase activity, the anti-melanogenic activity of resorcinol in B16F10 cells has been attributed to the inhibition of cAMP signaling and activation of p38 MAPK [179]. The same applies e.g., to moracin J [181], 4,5-dicaffeoylquinic acid [183], chrysin [187], casuarictin [178], and synthetic compounds [135,136,153,197], which have been reported to both inhibit intracellular tyrosinase activity and regulate melanogenesis-related protein expression.…”
Section: Human and Animal Tyrosinase Phenolic Inhibitorsmentioning
confidence: 99%
“…The extract exhibited inhibitory activity for the enzyme, with an IC50 of 238.10 ± 15.51 µg/mL, compared to the IC50 value obtained for arbutin of 193.84 ± 14.15 µg/mL. Ellagitannins, ellagic acid, and its derivatives present in the extract could be responsible for this effect since these compounds are known to inhibit tyrosinase, mainly by cooper quelation [27,28]. Other effects attributed to these phenolic compounds, including the suppression of enzyme expression and antioxidant activity, could also contribute to the decrease in melanin formation [11].…”
Section: Evaluation Of Tyrosinase Inhibitory Activity Of the Extractmentioning
confidence: 81%
“…The ellagitannins were predominant in the extract and could be responsible for the tyrosinase inhibition. Previous studies reported the antimelanogenic activity of these compounds [11,27].…”
Section: Total Tannin Content In Extract and Hydrogel Formulationmentioning
confidence: 99%
“…The direct effect of CBA on diphenolase activity was tested using mushroom tyrosinase as a source of enzyme activity with L-DOPA substrate while the effects on monophenolase activity were tested using L-TYR substrate based on the method reported in our earlier study [20]. Briefly, 80 µL aliquots of CBA, prepared at different concentrations in 50 mM sodium phosphate (pH 6.8) buffer, were added to a 96-well microplate, followed by 100 µL of freshly prepared substrate solution (6 mM L-DOPA in phosphate-buffered saline).…”
Section: In Vitro Diphenolase and Monophenolase Activitymentioning
confidence: 99%